2017
DOI: 10.1038/ncomms15434
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic CuMnAs multi-level memory cell with microelectronic compatibility

Abstract: Antiferromagnets offer a unique combination of properties including the radiation and magnetic field hardness, the absence of stray magnetic fields, and the spin-dynamics frequency scale in terahertz. Recent experiments have demonstrated that relativistic spin-orbit torques can provide the means for an efficient electric control of antiferromagnetic moments. Here we show that elementary-shape memory cells fabricated from a single-layer antiferromagnet CuMnAs deposited on a III–V or Si substrate have determinis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(162 citation statements)
references
References 20 publications
2
155
1
Order By: Relevance
“…36(a) and 38]: in CuMnAs via global electrical measurements (anisotropic magnetoresistance) Olejnik et al, 2017a) as well as via local direct imaging of the antiferromagnetic domains (x-ray magnetic linear dichroism photoelectron emission microscopy) (Grzybowski et al, 2017), and in Mn 2 Au via global electrical measurements (anisotropic magnetoresistance) (Bodnar et al, 2017;Meinert, Graulich, and Matalla-Wagner, 2017). CuMnAs and Mn 2 Au crystals possess local inversion symmetry breaking in bulk crystal, as explained (see also Table III), and display anisotropic magnetoresistance allowing for the electrical detection of the order parameter orientation.…”
Section: A Manipulation By Inverse Spin Galvanic Torquementioning
confidence: 99%
“…36(a) and 38]: in CuMnAs via global electrical measurements (anisotropic magnetoresistance) Olejnik et al, 2017a) as well as via local direct imaging of the antiferromagnetic domains (x-ray magnetic linear dichroism photoelectron emission microscopy) (Grzybowski et al, 2017), and in Mn 2 Au via global electrical measurements (anisotropic magnetoresistance) (Bodnar et al, 2017;Meinert, Graulich, and Matalla-Wagner, 2017). CuMnAs and Mn 2 Au crystals possess local inversion symmetry breaking in bulk crystal, as explained (see also Table III), and display anisotropic magnetoresistance allowing for the electrical detection of the order parameter orientation.…”
Section: A Manipulation By Inverse Spin Galvanic Torquementioning
confidence: 99%
“…The electrical switching in antiferromagnetic bit cells can be combined with the electrical readout via ohmic anisotropic magnetoresistance, which, in present devices, is of the order of ~1% [154][155][156]. Previously, ~100% magnetoresistance was demonstrated in tunneling devices with antiferromagnetic electrodes and where the reorientation of antiferromagnetic moments was controlled by a magnetic field via an attached ferromagnet [154].…”
Section: Electrical Reading Of Information In Antiferromagnetsmentioning
confidence: 99%
“…CuMnAs, Mn 2 Au), a local relativistic field is generated, which points in the opposite direction on magnetic atoms with opposite magnetic moments. The resulting field-like Néel spin-orbit torque has been demonstrated to allow for a reversible switching of antiferromagnetic moments in microelectronic bit cells by electrical current pulses of a length ranging from milliseconds to picoseconds [155,156]. The key challenge in the Néel spin-orbit torque switching is keeping the current density sufficiently low when downscaling the pulse-length in order to realize energy efficient, ultrafast electrical writing of information in antiferromagnets.…”
Section: Current and Future Challenges Electrical Writing Of Informamentioning
confidence: 99%
See 1 more Smart Citation
“…Further it was shown that the magnetic domain orientation was correlated to the electrical resistance 6 and used in a multilevel memory device. 7 Both exchange-bias and AF dynamics depend on the AF domain structure, hence a detailed understanding of domain formation and possibly domain engineering are both essential for further device development. 1,5,8 The mechanisms responsible for domain formation in AF materials are not as straightforward as in the case of FM materials, since there is no macroscopic demagnetizing field.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%